Differences in cisplatin distribution in sensitive and resistant ovarian cancer cells: a TEM/NanoSIMS study. Issue 10 (15th September 2017) - Lee, Ronald F. S.; Riedel, Tina; Escrig, Stéphane; Maclachlan, Catherine; Knott, Graham W.; Davey, Curt A.; Johnsson, Kai; Meibom, Anders; Dyson, Paul J.
Abstract : Cisplatin is a widely used anti-cancer drug, but its effect is often limited by acquired resistance to the compound during treatment. Abstract : Cisplatin is a widely used anti-cancer drug, but its effect is often limited by acquired resistance to the compound during treatment. Here, we use a combination of transmission electron microscopy (TEM) and nanoscale-secondary ion mass spectrometry (NanoSIMS) to reveal differences between cisplatin uptake in human ovarian cancers cells, which are known to be susceptible to acquired resistance to cisplatin. Both cisplatin sensitive and resistant cell lines were studied, revealing markedly less cisplatin in the resistant cell line. In cisplatin sensitive cells, Pt was seen to distribute diffusely in the cells with hotspots in the nucleolus, mitochondria, and autophagosomes. Inductively coupled plasma mass spectrometry (ICP-MS) was used to validate the NanoSIMS results.